From rhizosphere to detritusphere: unraveling the fate of root carbon inputs in the soil - Teixeira, Pedro Paulo de Carvalho (2021)
The conversion of root carbon (C) into soil organic matter (SOM) is regarded as the “hidden half” of the terrestrial C cycle. Nevertheless, recent evidence shows that root C inputs exert an important role in SOM formation , although the reasons behind these results are not understood. Roots create two temporally separated hotspots for carbon cycling in the soil: the rhizosphere, which is shaped by living roots C inputs, and the detritusphere, which is formed after root death. The succession between rhizosphere and detritusphere can affect the incorporation of these C inputs in MOS and can be an important mechanism to explain the high efficiency of root C inputs to form SOM. The general objective of this work was to gain knowledge about the processes that control the conversion of rhizodeposition and root litter C into SOM. To this end, we designed two complementary studies that simulate the sequential root C inputs in the soil, f rom the rhizosphere (Chapter 1) to the rhizosphere-detritusphere transition (chapter 2). We employed isotopic techniques (double labeling of 13 C and 15 N) to follow the fate of Eucalyptus spp. rhizodeposits and root litter in a Rhodic Ferralsol. Our results show that the persistence of rhizodeposit-derived C (rhizo-C) and root litter C is given by distinct mechanisms. More than 70% of recovered rhizo-C present in the soil was retained in the mineral-associated fraction (MAOM), and about 90% of this fraction persisted in the soil after 166 days of incubation. This result attests that rhizodeposits are capable to form persistent SOM through mineral associations. However, we observed that only a minor quantity of rhizo-C was incorporated with organo-metallic complexes and short-range order phases of iron and aluminum. In contrast to rhizo-C, the majority of root litter C remained in particulate fractions and about 10% of decomposed root litter C was incorporated in to SOM. Further, we observed that rhizo- C concentrated more closer to roots, but was detected even up to 25 mm away. This result is evidence that rhizo-C can have a wider distribution in the soil volume in comparison to root litter, whose transfer was restricted to the first 4 mm from its surroundings. The root litter inputs tended to favor the fungal community, which is more adapted to process more complex C sources and can directly assimilate C from the litter layer. Furthermore, from the NanoSIMS (Nanoscale Secondary Ion Mass Spectrometry) results, we provide direct evidence for the incorporation of root litter into microbial structures and the formation of mineral-associated SOM at the detritusphere. Still, we observed that the decomposition of root litter and rhizo-C occurred independently in the rhizosphere-detritusphere transition. This result suggests that different microbial groups are responsible to process each type of root C input. Overall, our holistic approach reveals the intricate dependence between plant, soil, and microorganisms in the formation of SOM, and reinforces the importance of rhizodeposits as a source of C stable SOM formation. Keywords: Eucalypt. Soil organic matter. Isotopes. NanoSIMS. Legacy effects. Phospholipid fatty acids.